Kinetic studies of ion-pairing effects on the aquation of chloropentaammine cobalt(III) complex in different dicarboxylate media at 30% of tert-butanol - Zeitouni, Farah Samih; Chaaban, Jinane Kamal; Hamed, Ramzi Kassem (European Journal of Chemistry, 2017)
The study of the kinetic aquation of chloropentaammine cobalt(III) ion in the presence of different types of dicarboxylate solutions (Malonate, malate, tartarate and succinate), in mixed solvent media of water with tert-butanol (30%, v:v) is investigated spectrophoto-metrically at different temperatures (30-60 °C) in the light of the effects of ion-pairing on reaction rates and mechanism. Comparison of the kip (Rate constant of ion-pairing) values with respect of different buffers (Malonate, malate, tartarate and succinate) at 30% of tert-butanol is introduced. Examination of the linear free energy relationship (LFER) at the mentioned conditions will lead to diagnosethe mechanism. The free energy of activation ΔG*ip is more or less linearly varied among the studied dicarboxylate ion-pairing ligands indicating the presence of compensation effect between ΔH*ip and ΔS*ip.